Expression of the Tobacco Non-symbiotic Class 1 Hemoglobin Gene Hb1 Reduces Cadmium Levels by Modulating Cd Transporter Expression Through Decreasing Nitric Oxide and ROS Level in Arabidopsis - Bahmani, Ramin; Kim, DongGwan; Na, JongDuk; Hwang, Seongbin (Frontiers in Plant Science, 2019)
Hemoglobin (Hb) proteins are ubiquitous in plants, and non-symbiotic class 1 hemoglobin (Hb1) is involved in various biotic and abiotic stress responses. Here, the expression of the tobacco (Nicotiana tabacum) hemoglobin gene NtHb1 in Arabidopsis (Arabidopsis thaliana) showed higher cadmium (Cd) tolerance and lower accumulations of Cd, nitric oxide (NO), and reactive oxygen species (ROS) like hydrogen peroxide (H2O2). NtHb1-expressing Arabidopsis exhibited a reduced induction of NO levels in response to Cd, suggesting scavenging of NO by Hb1. In addition, transgenic plants had reduced accumulation of ROS and increased activities of antioxidative enzymes (catalase, superoxide dismutase, and glutathione reductase) in response to Cd. While the expression of the Cd exporters ABC transporter (PDR8) and Ca2+/H+ exchangers (CAXs) was increased, that of the Cd importers iron responsive transporter 1 (IRT1) and P-type 2B Ca2+ ATPase (ACA10) was reduced in response to Cd. When Col-0 plants were treated with the NO donor sodium nitroprusside (SNP) and H2O2, the expression pattern of Cd transporters (PDR8, CAX3, IRT1, and ACA10) was reversed, suggesting that NtHb1 expression decreased the Cd level by regulating the expression of Cd transporters via decreased NO and ROS. Correspondingly, NtHb1-expressing Arabidopsis showed increased Cd export. In summary, the expression of NtHb1 reduces Cd levels by regulating Cd transporter expression via decreased NO and ROS levels in Arabidopsis.